Identification of non-coding RNA related prognosis biomarkers based on ceRNA network in thyroid cancer - Fang, Xin; Chen, Xiliang; Gao, Jingquan; Tong, Liquan (Frontiers in Genetics, 2023)
Thyroid cancer (THCA) has become a serious malignant tumor worldwide. Identification of non-coding RNA related regulators is very necessary to improve the knowledge of THCA treatment. The aim of this study was to identify novel therapeutic targets and prognosis biomarkers for predicting pathological characteristics and subsequently treating THCA. We firstly identified that miR-4709-3p and miR-146b-3p could significantly classify patients into high/low risk groups, which may be potential prognosis biomarkers of THCA. Secondly, we constructed a THCA-related miRNA-mRNA network, which displayed small world network topological characters. Two THCA-related functional modules were identified from the miRNA-mRNA network by MCODE. Results showed that two modules could implicate in known cancer pathways, such as apoptosis and focal adhesion. Thirdly, a THCA-related miRNA-lncRNA network was constructed. A subnetwork of miRNA-lncRNA network showed strong prognosis effect in THCA. Fourthly, we constructed a THCA-related mRNA-lncRNA network and detected several typical lncRNA-miRNA-mRNA crosstalk, such as AC068138, BCL2, miR-21 and miR-146b, which had good prognosis effect in THCA. Furthermore, we evaluated the crosstalk activity between lncRNA expression and tumor immune cell infiltration. Immune infiltration results showed that lncRNAs LA16c−329F2, RP11−395N3, RP11−423H2, RP11−399B17 and RP11−1036E20 were high related to neutrophil and dendritic cell infiltration. Summarily, non-coding RNA mediated gene regulatory network has the strong regulatory potential in pathological processes of THCA. All these results could help us uncover the non-coding RNA mediated regulatory mechanism in THCA.